The design and making of a micro-cut boring unit / Saharuddin Shamsussin, Johari Sahat and Ab. Khalik Parman - Shamsussin, Saharuddin; Sahat, Johari; Parman, Ab. Khalik (2023)
This project concerns the design and making of a vertical boring tool normally to be fixed on a drilling machine, using the drilling machine as a source of driving power. It can also be fitted on the milling machine. This boring tool can be used for the final operation or a preliminary to grinding and other sizing operations. Another function is to give a relatively small scale diameter of the hole to be bored i.e. for the bearing housing.